PENGARUH BEBAN KERJA;PENGEMBANGAN KARIER; DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI SEKOLAH TINGGI SANDI NEGARA - Hutagalung, Mardiana Israkiyah; Kasmir, Kasmir (Universitas Mercu Buana, 2017)
This study aims to analyze the effect of work load; career development and discipline on the performance of civil servants at National Crypto Institute. Research data from questionnaire and secondary data. The sampling method used was probability sampling. From a population of 133 people; 100 people become the sample. The method of analysis used in this study is multiple linear regression. The result showed thatÂ work load; career development and discipline simultaneously are having significant influence to the performance of civil servants at National Crypto Institute. Partially work load and discipline has positive significant effect on the performance; while career development has a significant negative effect. Discipline is the biggest significant variable in influencing the performance of civil servants at National Crypto Institute while work load has medium significant variable in influencing the performance.